Two new species of Leptarma (Decapoda, Brachyura, Sesarmidae) from the Western Indian Ocean with notes on their phylogeny - Shahdadi, Adnan; Schubart, Christoph D. (Zootaxa, 2020)
Two new species of Leptarma, L. dispersum n. sp. and L. reunionense n. sp. are described from Europa Island and Réunion Island, respectively. Genetically, based on the mitochondrial COX1 gene, both species are markedly divergent from other congeneric species. Phylogenetically, L. dispersum n. sp. shows close relationship with L. lenzii (De Man, 1895) while L. reunionense n. sp. clusters with L. aurifrons (Li, Ng & Shih, 2019) and the species pair L. moluccense (De Man, 1892) and L. paucitorum (Rahayu & Ng, 2009). Morphologically, the new species differ most significantly from congeners by the relative length of the ambulatory legs and the shapes of the first gonopods and carapace. After the description of these two new species, the number of species comprised in the genus Leptarma is raised to 20, four of them being distributed in and off East Africa.